Aspectos metalúrgicos de revestimentos dissimilares com a superliga à base de níquel inconel 625 - Silva, Cleiton Carvalho (2022)
To extend the life and reliability of pipes and equipment in oil & gas production and processing settings is a continuous demand. These aspects are essentially dependent on corrosion resistant alloys used. In this context, the weld overlay with Ni-based superalloys is a great interesting alternative, since improve the corrosion resistance without increase the cost of manufacture when compared to massive equipment. Thus, the objective of this study was to evaluate the metallurgical aspects of Inconel 625 weld overlays deposited by GTAW cold wire feed process. The welds were performed using a robotic workbench, an electronic power supply and a data acquisition system. The microstructural characterization was carried out using scanning electron microscopy (SEM), transmission electron microscopy (MET), electron dispersive spectroscopy (EDS) and X-ray diffraction. The results shown that the microstructure of overlays was formed by a gamma matrix and secondary phases rich in Nb. These precipitates were identified as Nb-rich Laves phase and a complex TiN/NbC.